Organic agriculture in Argentina’s Pampas. A case study on Pampa Orgánica Norte farmers - Cabrini, Silvina María; Elustondo, Luciana (Cambridge University Press, 2022)
Faced with a society that demands the reduction of negative environmental impacts of agriculture while producing high-value, healthy food for local and export markets, Argentina is currently in a debate on the alternative paths toward sustainability in agricultural production. Argentina is ranked second in the world in terms of land under organic certification. Extensive sheep production in Patagonia natural grasslands accounts for most of this area and harvested organic area remains a very small fraction of total harvested land (0.6%). This paper aims to contribute to the discussion of opportunities and limitations in organic farming as an ecological intensification alternative for Argentina’s Pampas. A case study was conducted on Pampa Orgánica Norte. This is a group of nine organic farmers that manages field crops and livestock-certified organic production. Farmers interviewed in this study considered different criteria including economic and environmental attributes when choosing to produce organically. However, the main drivers for conversion to organic production are related to environmental factors, in particular ecosystem protection. The main limitations in organic production are related to crop management practices, primarily weed control. To achieve the goal of increasing organic production a more active role of the public sector in technology generation and transfer was demanded by farmers.